2018
DOI: 10.1002/nau.23495
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant defunctionalized bladder—overrated condition?

Abstract: Gene expression of bladder receptors involved in micturition control was similar in patients with or without DB. Bladder behavior had a similar pattern independently of pretransplant residual diuresis. These findings question the relevance of the term DB in pretransplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This is no longer widely practiced as studies have consistently shown that kidneys can be safely transplanted into defunctionalized bladders (DB), which regain normal capacity and compliance within 1 year of KT [19][20][21]. Contemporarily, in 2018, Neves Neto et al biopsied bladder mucosa and detrusor samples in 33 patients with defunctionalized bladders and 35 patients with normal bladders (diuresis < 300 vs. > 300 mL/24 h) to compare receptor mRNA levels commonly altered in LUT dysfunction [22]. Apart from a 2.8-fold overexpression of the α 1D adrenergic receptor (p = 0.018) in the defunctionalized bladder cohort, there were no other statistically significant differences in gene expression.…”
Section: Defunctionalized Bladders and Bladder Cyclingmentioning
confidence: 99%
“…This is no longer widely practiced as studies have consistently shown that kidneys can be safely transplanted into defunctionalized bladders (DB), which regain normal capacity and compliance within 1 year of KT [19][20][21]. Contemporarily, in 2018, Neves Neto et al biopsied bladder mucosa and detrusor samples in 33 patients with defunctionalized bladders and 35 patients with normal bladders (diuresis < 300 vs. > 300 mL/24 h) to compare receptor mRNA levels commonly altered in LUT dysfunction [22]. Apart from a 2.8-fold overexpression of the α 1D adrenergic receptor (p = 0.018) in the defunctionalized bladder cohort, there were no other statistically significant differences in gene expression.…”
Section: Defunctionalized Bladders and Bladder Cyclingmentioning
confidence: 99%